2022
DOI: 10.1186/s12906-022-03609-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective effects of Sargassum thunbergii on ultraviolet B-induced mouse L929 fibroblasts and zebrafish

Abstract: Background Chronic exposure to ultraviolet B (UVB) causes a series of adverse skin reactions, such as erythema, sunburn, photoaging, and cancer, by altering signaling pathways related to inflammation, oxidative stress, and DNA damage. Marine algae have abundant amounts and varieties of bioactive compounds that possess antioxidant and anti-inflammatory properties. Thus, the objective of this study was to investigate the photoprotective effects of an ethanol extract of Sargassum thunbergii. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…T‐SOD and CAT are important components of the antioxidant system in the body (51). Compared with the control group, the activities of T‐SOD and CAT enzymes in zebrafish were significantly decreased after UVB treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T‐SOD and CAT are important components of the antioxidant system in the body (51). Compared with the control group, the activities of T‐SOD and CAT enzymes in zebrafish were significantly decreased after UVB treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, neutrophils migrated to zebrafish fins may be one of important causes in zebrafish photoaging. of linseed orbitides on antioxidant enzyme activity in UVB-treated zebrafish T-SOD and CAT are important components of the antioxidant system in the body (51). Compared with the control group, the activities of T-SOD and CAT enzymes in zebrafish were significantly decreased after UVB treatment.…”
Section: Linseed Orbitides Inhibit Migration Of Neutrophils In Uvbtre...mentioning
confidence: 93%
“…Therefore, studying the impact of light on skin cells is crucial for the development of skin health care and the treatment of skin diseases. Fibroblasts are the most common connective tissue cells in the body and are frequently used in light studies [78,79]. Studies have revealed that light has a notable effect on the proliferation and differentiation of fibroblasts and can regulate the extracellular matrix produced by them.…”
Section: Frequency and Wavelength Principle Applicationmentioning
confidence: 99%
“…S. horneri extract contained 7.45 ± 0.29% of total phenolics and 0.29 ± 0.07% of total flavonoids. In a different model using UV-irradiated zebrafish embryos, a polyphenol-rich ethanolic extract from S. thunbergii , demonstrated a decrease (at 0.8 µg/mL, 1.2 µg/mL, and 1.6 μg/mL concentrations, respectively) in ROS production by 71%, 71%, and 85%, respectively [ 119 ]. Fucoxanthin and the meroterpenoid tetraprenyltoluquinol chromane, isolated from S. siliquastrum and S. muticum, respectively, showed a similar trend in human dermal fibroblasts exposed to the same radiation [ 53 , 120 ].…”
Section: Bioactive Potential Of Sargassum Antioxidant Secondary Metab...mentioning
confidence: 99%